Systematics of the bee subgenus Systropha (Austrosystropha) (Hymenoptera: Halictidae): Description of a new species and proposal of a new sex association - Patiny, Sebastien; Baldock, David; Michez, Denis (Zootaxa, 2013)
Systropha is a small genus of bees belonging to Rophitinae (sister-group to all remaining Halictidae). Three subgenera are recognized in Systropha: Austrosystropha and Systrophidia that are sub-Saharan endemics, and Systropha s.str., which oc-curs in Africa and Eurasia. As a result of the rarity of Systropha specimens in collections and the difficulty in associating males and females due to sexual dimorphism, there remain numerous undescribed or unassociated sexes in S. (Austrosys-tropha). The present paper gives the descriptions of a new species Systropha oti sp. n. (from Kenya) and the previously undescribed female of S. aethiopica, both in the subgenus Austrosystropha. We further discuss the diagnostic features of the subgenus with regard to these new taxa and update the previous key to species.